Pengukuran Beban Kerja Fisik dan Beban Kerja Mental Karyawan Divisi Pertenunan Menggunakan Metode % Cardiovascular Load (% CVL) dan NASA-TLX di PT XYZ - Anisa Azzahra; Anita Oktaviana Trisna Devi; Agung Widyanto F S (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2026)
Low productivity and high sick leave in the weaving division of PT XYZ in Yogyakarta are caused by excessive physical and mental workload on Shuttle Loom Unit 2 operators. The productivity of the weaving division of PT XYZ was recorded at only 61.96% (target 75%) with sick leave of 4.17%, indicating operator fatigue. This study measured physical workload using the Cardiovascular Load (CVL) method based on heart rate and mental workload using NASA-TLX, and analyzed the correlation with age and length of service. The results showed a moderate physical workload category (40% light CVL <30, 60% moderate 30-60) at a temperature of 30.5°C, and high-very high mental workload (45% high 50-79, 55% very high ≥80, average EF 79.3) due to strict quality targets (0.5% defects). There is a correlation between CVL and NASA-TLX with age. Recommendations include reducing the daily production target from 100 to 85-88 yards, optimizing ergonomics, and training to reduce EF to 65 and defects to 0.3, to increase effective productivity.